Vortex structure identification for supersonic flows. (October 2020) - Borisov, V E; Davydov, A A; Konstantinovskaya, T V; Lutsky, A E
Abstract: This work is devoted to the application of vortex structure identification methods for two counter-rotating wingtip vortices in a supersonic flow. The λ2 criterion and the method of maximum vorticity were used for detection vortex core lines and visualization of vortex sheet and rope. Computational model based on the URANS equations with SA turbulence model was applied. Numerical simulations were performed on the hybrid supercomputing system K-60 at the Keldysh Institute of Applied Mathematics RAS using the developed software package ARES for 3D turbulent flows modeling on high performance computing systems.